Economic diplomacy in the system of supporting Ukraine’s foreign economic activity - Natalia Galaziuk; Оlha Zelinska (Економічний форум, 2024)
The international environment is characterised by a dynamic nature, a steady trend towards quantitative growth and qualitative development, which necessitates a more cautious and balanced approach to the choice of foreign economic policy, given the complexity of the structure of the world economy, the system of international economic relations, regulation and management. The purpose of the article was to study the conditions for ensuring Ukraine’s foreign economic activity through the influence of economic diplomacy and to identify tools for defending the country’s national economic interests on the world stage. The methodological basis of the study was the tools of historical and logical approaches, analysis, statistical and graphical methods. The article examined the theoretical and conceptual foundations of economic diplomacy, namely: the essence and importance of economic diplomacy in international economic relations were characterised; economic diplomacy as an element of the system of management of the country’s foreign economic activity was studied; the mechanism of achieving national competitiveness through economic diplomacy was outlined. The Ukrainian experience of functioning of the economic diplomacy mechanism was analysed, in particular: the analysis of economic diplomacy in the system of national economic security of Ukraine, the analysis of institutional support for the implementation of Ukraine’s foreign economic potential. A new paradigm of economic diplomacy of Ukraine was also developed to ensure competitive advantages: the main prospects of economic diplomacy in the context of Ukraine’s European integration course were identified, the possibility of increasing Ukraine’s international competitiveness through economic diplomacy mechanisms was substantiated. The practical value of the research results lies in the fact that the formulated theoretical provisions, conclusions and recommendations can be used: in the scientific and research sphere for conducting further scientific research on strategic ways to increase the competitiveness of the national economy in modern economic conditions; in regulatory activities for developing regulatory legal acts and improving the legislation of Ukraine in the direction of diplomacy in the conditions of dynamic development of the international environment; in the educational process during the preparation of textbooks and teaching aids on international economic relations